(untitled) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2019)
Women and gender studies in academic institutions have a recent history (herstory). The first efforts took place in the early 1980’s. The objective of this article is to analyze that trajectory, from the link with the feminist movement. In the first place, some background is analyzed. The organisations that, at the begining of the 20th century, placed at the centre of the political debate the sufrage and the recognition of women’s citizenship are mentioned. In a second moment, the so-called feminist movement of the second wave is analyzed: its main demands and the dialogue with the State. Finally, three academic experiences are described: El Colegio de México (The College of Mexico), the Universidad Nacional Autónoma de México (National Autonomous University of Mexico) and the Universidad Autónoma Metropolitana unidad Xochimilco (Metropolitan Autonomous University campus Xochimilco). The creation of ad hoc spaces was posible because the feminist movement had reached enough strength to be a recognised social actor.